Academic Senate Minutes 2008-12-04 - Academic Senate:::::::::
Announcement and Chair Report. Correspondence received. Agenda approved. Minutes of 11/13 approved. New minor in Early Childhood Education approved. WASC update. Associated Students Report. Vice President of SAEM report. Special Statement from Joyce Chong, Managing Director, Advising, Career & EOP Services. Committee of the Whole discussion about the enrollment crisis. Motion that the Academic Senate of Sonoma State University requests that the Chief Financial Officer search for and find any and all one-time funds to restore instructional sections. Approved.